Clinical Result of Epicardial Pulmonary Vein Isolation (LAVIE) by Cryoablation as Concomitant Cardiac Operation and Clinical Application of New Ablation Device (KIRC-119 Infrared Coagulator) to Treat Atrial Fibrillation - Kubota, Hiroshi; Sudo, Kenichi; Takamoto, Shinichi; Endo, Hidehito; Tsuchiya, Hiroshi; Yoshimoto, Akihiro; Takahashi, Yu; Inaba, Yusuke; Furuse, Akira (IntechOpen, 2012)
None